Ageism in health care: A systematic review of operational definitions and inductive conceptualizations - São José, José (2020)
Purpose International and national bodies have identified tackling ageism in health care as an urgent goal. However, health professionals, researchers, and policy makers recognize that it is not easy to identity and fight ageism in practice, as the identification of multiple manifestations of ageism is dependent on the way it is defined and operationalized. This article reports on a systematic review of the operational definitions and inductive conceptualizations of ageism in the context of health care. Design and Methods We reviewed scientific articles published from January 1995 to June 2015 and indexed in the electronic databases Web of Science, PubMed, and Cochrane. Electronic searches were complemented with visual scanning of reference lists and hand searching of leading journals in the field of ageing and social gerontology. Results The review reveals that the predominant forms of operationalization and inductive conceptualization of ageism in the context of health care have neglected some components of ageism, namely the self-directed and implicit components. Furthermore, the instruments used to measure ageism in health care have as targets older people in general, not older patients in particular. Implications The results have important implications for the advancement of research on this topic, as well as for the development of interventions to fight ageism in practice. There is a need to take into account underexplored forms of operationalization and inductive conceptualizations of ageism, such as self-directed ageism and implicit ageism. In addition, ageism in health care should be measured by using context-specific instruments.